Doctors without Borders? Relicensing Requirements and Negative Selection in the Market for Physicians - Kugler, Adriana D.; Sauer, Robert M. (Journal of Labor Economics, 2005)
Relicensing requirements for professionals who move across borders are widespread. In this article, we measure the effects of occupational licensing by exploiting an immigrant physician retraining assignment rule. Instrumental variables and quantile treatment effects estimates indicate large returns to acquiring an occupational license and negative selection into licensing status. We also develop a model of optimal license acquisition that, together with the empirical results, suggests that stricter relicensing requirements may lead not only to practitioner rents but also to lower average quality of service in the market for physicians.